Enhancement of bacteriocin production by Lactobacillus plantarum strain I-UL4 and RS5 through optimisation of cultural conditions in different sizes of stirred tank bioreactors - Ooi, May Foong (2017)
Postbiotic is defined as the bioactive metabolites produced by probiotic lactic acid bacterium (LAB) which mediates beneficial probiotic effects. The postbiotics produced by Lactobacillus plantarum strains I-UL4 and RS5 are found important for various industrial applications. The postbiotic produced by Lactobacillus plantarum I-UL4 (postbiotic I-UL4) was found to have high potential as human health supplement and as in-feed additive to replace antibiotic growth promoter for Tilapia fish in aquaculture industry. Meanwhile, the postbiotic produced by Lactobacillus plantarum RS5 (postbiotic RS5) emerged as promising feed supplement for broilers and laying hens in livestock industry. One of the prominent attributes of postbiotic as alternative in-feed growth promoter is its antimicrobial activity. Bacteriocin is one of the postbiotic compounds contributes to the antimicrobial activity of postbiotic. However, the production of bacteriocin is not naturally optimised for maximum production rates and it was affected by cultural conditions encompass medium composition and physical parameters. Besides, the optimum condition for bacteriocin production by LAB was also found strain-dependent. There is no optimisation study has been conducted to enhance the bacteriocin-inhibitory activity of postbiotic I-UL4 and postbiotic RS5. In view of the importance to meet the need for different industrial applications, it is crucial to optimise the cultural conditions for enhancement of bacteriocininhibitory activity of postbiotic I-UL4 and postbiotic RS5 respectively. The optimisation study for cultural conditions which involves a huge number of experiments is more practical to be conducted in small scale cultivation using universal bottle. However, to determine the feasibility of production for industrial application, it is paramount to check the reproducibility of optimised cultural conditions in bioreactor level. Therefore, the general objective of this study was to enhance the bacteriocin-inhibitory activity of postbiotic I-UL4 and postbiotic RS5. The first and second specific objectives were to optimise the cultural conditions for the production of bacteriocin-inhibitory activity of postbiotic I-UL4 and postbiotic RS5 in universal bottle by using combination approaches of “one factor at a time” and response surface methodology. The optimised culture condition has enhanced bacteriocin-inhibitory activity of postbiotic I-UL4 to 100% in comparison to the activity achieved in de Man Rogosa Sharpe (MRS) medium. The bacteriocin-inhibitory activity of postbiotic I-UL4 achieved 1440 MAU/mL when L. plantarum I-UL4 was cultivated in optimised medium at 27 oC, initial pH at 6.72 and inoculum of 6.60 % (v/v). The optimised medium comprised of 20 g/L glucose, 36.20 g/L of yeast extract, 3.75 g/L of sodium acetate, 0.76 g/L of tween 80 and 0.03 g/L of manganese sulphate terahdyrate. For L. plantarum RS5, the optimised culture condition has enhanced bacteriocin-inhibitory activity to 112.5 % as compared to MRS medium. The bacteriocin-inhibitory activity of postbiotic RS5 was increased to 1360 MAU/mL when cultivated in optimised medium at 30 oC, initial pH at 6.40 and inoculum of 5.22 % (v/v). The optimised medium for L. plantarum RS5 consists of 20 g/L of glucose, 27.84 g/L of yeast extract, 5.75 g/L of sodium acetate, 1.12 g/L of tween 80 and 0.05 g/L of manganese sulphate terahydrate. The third specific objective was to determine the optimum agitation speed for 2 L batch cultivation of L. plantarum I-UL4 and L. plantarum RS5 using optimised medium and physical parameters in stirred tank bioreactor. The maximum level of bacteriocin-inhibitory activity (1440 MAU/mL), product yield coefficient of bacteriocin-inhibitory activity (100.28 x103 MAU/g) and biomass (5.54 g/L) were achieved when L. plantarum I-UL4 was cultivated at optimum agitation speed of 100 rpm under anaerobic condition. Meanwhile, the maximum level of bacteriocin-inhibitory activity (1600 MAU/mL), product yield coefficient of bacteriocin-inhibitory activity (87.15 x 103 MAU/g) and biomass (3.59 g/L) were achieved when L. plantarum RS5 was cultivated at optimum agitation speed of 150 rpm under anaerobic condition. The corresponding impeller tip speed for L. plantarum I-UL4 and L. plantarum RS5 was 0.34 m/s and 0.50 m/s respectively based on respective optimum agitation speed. The last specific objective was to scale-up the production of bacteriocininhibitory activity of postbiotic I-UL4 and postbiotic RS5 using optimised cultural conditions in 20 L batch cultivation based on constant impeller tip speed. For both L. plantarum strains, same level of maximum bacteriocin-inhibitory activities and comparable kinetic parameter values were achieved in 2 L and 20 L batch cultivations respectively, indicating the production of postbiotic I-UL4 and postbiotic RS5 were successfully scale-up based on constant impeller tip speed.